1988
DOI: 10.1111/j.1476-5381.1988.tb11444.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the novel anti‐anginal compound RS 43285 on myocardial conduction in the anaesthetized dog

Abstract: 1 A pentobarbitone-anaesthetized canine model ofmyocardial conduction was developed to evaluate drug effects on intra-atrial (I-A), intra-ventricular (I-V) and atrioventricular (A-V) conduction parameters, both at rest and during electrical pacing of the right atrium or ventricle. Drug effects on the ability of the sino-atrial (SA) node to re-establish sinus rhythm on switching off electrical pacing were also considered. The effects of the novel anti-anginal compound RS 43285-193 ((± )-N-(2,6-dimethylphenyl)-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Our earlier studies with verapamil in the critical stenosis model also showed activity for this drug at low doses (Alps et al, 1985). The doses producing S-T segment reduction and those producing detrimental myocardial conduction effects (400pgkg-m in the present study with a pacing frequency-dependent atrioventricular block at 100-400upgkg-1 in a previous study -Allely .& Alps, 1988) do not appear to be very well separated. Lew & Ban-Hayashi (1985) demonstrated that by elevating LVEDP above the ischaemia-induced increase, the global mechanical disadvantage imposed by the ischaemic zone was diminished.…”
Section: Discussionsupporting
confidence: 51%
“…Our earlier studies with verapamil in the critical stenosis model also showed activity for this drug at low doses (Alps et al, 1985). The doses producing S-T segment reduction and those producing detrimental myocardial conduction effects (400pgkg-m in the present study with a pacing frequency-dependent atrioventricular block at 100-400upgkg-1 in a previous study -Allely .& Alps, 1988) do not appear to be very well separated. Lew & Ban-Hayashi (1985) demonstrated that by elevating LVEDP above the ischaemia-induced increase, the global mechanical disadvantage imposed by the ischaemic zone was diminished.…”
Section: Discussionsupporting
confidence: 51%
“…Very little is known about the effects of ranolazine on cardiac electrophysiology. Although Allely & Alps (1988) did not find any effect of ranolazine on myocardial conduction in anesthetized dogs, clinical trials have shown a slight but clear prolongation of the QT interval in the ECG (Chaitman et al, 2004a, b). Drug-induced long QT syndrome.…”
Section: Introductionmentioning
confidence: 97%
“…Ranolazine (RS-43285) [10] is a clinically used anti-anginal drug [1113] that has also been shown to reduce ischemic damage in animal models [1416]. The specific cardioprotective mechanism(s) of ranolazine is not well understood especially since, and contrary to other antianginal agents, it exerts its effects without significantly changing hemodynamic parameters [17].…”
Section: Introductionmentioning
confidence: 99%